2019
DOI: 10.1038/s41467-019-13185-3
|View full text |Cite
|
Sign up to set email alerts
|

The wax gourd genomes offer insights into the genetic diversity and ancestral cucurbit karyotype

Abstract: The botanical family Cucurbitaceae includes a variety of fruit crops with global or local economic importance. How their genomes evolve and the genetic basis of diversity remain largely unexplored. In this study, we sequence the genome of the wax gourd (Benincasa hispida), which bears giant fruit up to 80 cm in length and weighing over 20 kg. Comparative analyses of six cucurbit genomes reveal that the wax gourd genome represents the most ancestral karyotype, with the predicted ancestral genome having 15 proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 63 publications
4
114
1
Order By: Relevance
“…Both protein BUSCO benchmark analysis 32 (ver. 3.0) and an InterProScan search 33 indicated that the Harukei-3 genome annotation represents a highly comprehensive dataset of plant protein-coding genes compared with published cucurbit genomes [26][27][28][34][35][36][37][38][39][40] (complete BUSCO = 1372 [95.3%] and InterPro ID count = 5607; Table 2 and Supplementary Data 1). In addition, we observed that our ONT-based gene prediction method gave accurate insights into exon-intron gene structure, whereas other methods (e.g., AUGUSTUS and Braker2) gave incorrect assessments of structure in some genes ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both protein BUSCO benchmark analysis 32 (ver. 3.0) and an InterProScan search 33 indicated that the Harukei-3 genome annotation represents a highly comprehensive dataset of plant protein-coding genes compared with published cucurbit genomes [26][27][28][34][35][36][37][38][39][40] (complete BUSCO = 1372 [95.3%] and InterPro ID count = 5607; Table 2 and Supplementary Data 1). In addition, we observed that our ONT-based gene prediction method gave accurate insights into exon-intron gene structure, whereas other methods (e.g., AUGUSTUS and Braker2) gave incorrect assessments of structure in some genes ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…>10 kb) emerged as an alternative approach. Many plant genomes have been assembled and/or re-evaluated using such newer DNA sequencers [22][23][24][25][26][27][28] , including the genome of the Chinese inodorus melon cultivar Payzawat, which was sequenced using a PacBio RSII platform 29 . In addition, such approaches can provide insights into genome structural variation, as was demonstrated in Solanum lycopersicum using ONT ultra-long sequencing technology 22 .…”
mentioning
confidence: 99%
“…The sponge gourd genome (656.19 Mb) is substantially larger than that of most other sequenced cucurbitaceous species (269-469 Mb) [13][14][15][16][17][18][19] but smaller than that of wax gourd (913 Mb) 12 . Sponge gourd shows much more obvious TE expansion (62.62%) than other cucurbitaceous species such as watermelon (45.2%) 13 , melon (14.7%) 14 , cucumber (24.4%) 15 , and bitter gourd (15.3%) 19 but similar TE expansion to wax gourd (66.18%) 12 . Accordingly, this expansion may have played a crucial role in the increase in the genome size of sponge gourd.…”
Section: The Evolution and Genome Characteristics Of Sponge Gourdmentioning
confidence: 99%
“…Cogn. (Xie et al, 2019). These advances have made it possible to understand the genetic architecture of seed size variation in cucurbits through QTL studies and genome-wide association analysis.…”
Section: Introductionmentioning
confidence: 99%